2010
DOI: 10.5251/abjna.2010.1.5.1031.1043
|View full text |Cite
|
Sign up to set email alerts
|

Water allocation and optimization of minor canal operation

Abstract: In this study a mathematical simulation of canal operation is presented for optimizing water allocation within a multiple crop rotation canal. Zero-one linear programming algorithm was made for optimal flow regulation and to optimize irrigation water allocation and sequencing of different outlets in the irrigation canal under the constraints of fixed canal capacity and irrigation interval. The model was coded in a personal computer using Excel -visual basic application language (VBA) and designed to serve as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…The water saving results are almost similar to those reported by Zhenmin (1992), who estimated about 28.5% water saving when canal was scheduled on 10 days instead of 14 with optimum water in China. The results of the study area are also in agreement with Mohamed et al (2010), who observed 33% in canal water saving when canals were operated on actual water duties and 50% water saving when they operated on design water duties. In the present case, the optimum water allocation to secondary canals has been allowed separately for kharif and rabi seasons rather than on a design basis.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The water saving results are almost similar to those reported by Zhenmin (1992), who estimated about 28.5% water saving when canal was scheduled on 10 days instead of 14 with optimum water in China. The results of the study area are also in agreement with Mohamed et al (2010), who observed 33% in canal water saving when canals were operated on actual water duties and 50% water saving when they operated on design water duties. In the present case, the optimum water allocation to secondary canals has been allowed separately for kharif and rabi seasons rather than on a design basis.…”
Section: Discussionsupporting
confidence: 90%
“…It was observed that the second and third methods with less variability in cluster demand were more efficient than the first CBIO method and save maximum volume of water. Results on canal scheduling through the second and third CBIO methods, in terms of water saving, are in close agreement with the results obtained by Zhenmin (1992) and Mohamed et al (2010) on Sunni canal in Sudan and the North main canal scheduling in China, respectively. The present scheduling would also save more water as compared to alternate scheduling (7-7 days) as designed by Mishra et al (2002Mishra et al ( , 2008, where 13 and 10.3% water saving was calculated.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations